Application of the Take and Give Method in Improving the Mastery of Arabic Mufrodat in Class IV A Students at MI al-Huda Karangnongko, Maguwoharjo - Siti Nurhasana Mokodompit; Agung Setiyawan (Universitas Muhammadiyah Enrekang, 2024)
A problem that still often occurs in the Arabic learning process is the lack of Arabic mufrodat vocabulary in students, this is because the methods used by teachers are conventional only centered on teachers, so this affects the grades of students who have not reached the KKM on average. This study aims to determine the influence of the Take and Give method to improve mastery of Arabic mufrodat. Research method, this study is an action research with a quantitative approach in this study the facilitator is the researcher, the researcher took a sample of class IV A MI al-Huda Karangnongko, Maguwoharjo which amounted to 22 people by looking at the results of the cycle. The data collection technique in this study is by using observation and test results. Based on the results of the analysis, it can be concluded that the mastery of the Arabic mufrodat using the Take and Give learning method in the process of its application has increased, where in the first cycle the final result was found to be 69%, while in the second cycle it increased to 87%. This shows that there is a significant influence on the application of the Take and Give method in mastering the Arabic mufrodat in grade IV A students of MI al-Huda Karangnongko, Maguwoharjo.